Linguistics Landscape in Project-based Learning and Its Effect on Students' Writing Skills in EFL Context - Maheswari, Anom Cynthia (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
Writing skills, as a one of difficult skills to be mastered by students need to be concerned in English learning. Students often struggle in mastering writing skills. The teacher needs to be considered teaching method and strategy in order to give an influence on the learning results of the students. This study aims to investigate the impact of applying the linguistics landscape technique on students' writing skills, employing a quantitative design with a pre-experimental one-group pre-test post-test design. The sample includes 38 7th-grade students from SMPN 1 Singaraja. Tests were administered before and after the treatment, and shows the improvement in the test result. The t-test results indicate a significant level below the alpha level (α = 0.05), providing additional evidence in accepted the hypothesis. The results indicated significant improvements in students' writing skills through the application of the linguistics landscape technique. In conclusion, the implementation of project-based learning with the integration of the linguistics landscape technique proves to be a significant enhancer of students' writing skills. The result of the study in combining Linguistics landscape technique and Project-based learning my give teacher with a new perspective in English teaching in form of writing.